Unique simultaneous dual mechanism based bilateral femoral head fracture secondary to posterior dislocation of hip: A rare case report - Gadi, Daksh; Singh, Ravinder; Anand, Vikas; Pathak, Subodh (International Journal of Medicine, 2015)
Hip joint being surrounded by strong ligaments and muscles is considered a stable joint and dislocations are exceptionally rare. Majority of the dislocations are unilateral and are secondary to a high velocity traumatic injury making a bilateral dislocation a rare entity. Due to high velocity injury, femur head and acetabular wall fractures have been associated to dislocations and each of the associated injuries occurs with a different mechanism of injury. In view of its rarity we hereby have reported a unique mechanism based case of bilateral posterior dislocation of hip with bilateral femoral head fracture.